Derecho a la vida privada: garantía constitucional restringida para los servidores públicos en Colombia (2019)
The main objective of this review article is to analyze the private lives of public and civil servants, and their behavior in the public sphere, with a focus on events that resulted in further investigation by the Colombian State with subsequent economic and legal sanctions due to actions underwent in their private lives. An inquiry was made through the means of hypothetical/deductive reasoning, documentary analysis and case studies of disciplinary regimes of the public force, their Disciplinary Code, among others, and their modifications through the jurisprudence of the Constitutional Court and the Council of State, in order demonstrate events in which public service participation was limited. One key finding was the identification of several faults in the disciplinary regimes of the National Police, the National Army, and the Sole Disciplinary Statute of Colombia. These faults allegedly do not constitute a substantial violation of the functional duties of public servants, since the behaviors typified therein do not contradict principles that govern public function. Thusly it would be possible to demonstrate that its inclusion in the law constitutes an affectation to the private life of the public servant.